No SARS‐CoV‐2 carriage observed in children attending daycare centers during the intial weeks of the epidemic in Belgium. Issue 3 (17th December 2020) - Desmet, Stefanie; Ekinci, Esra; Wouters, Ine; Decru, Bram; Beuselinck, Kurt; Malhotra‐Kumar, Surbhi; Theeten, Heidi
Abstract: To gain knowledge about the role of young children attending daycare in the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) epidemic, a random sample of children ( n  = 84) aged between 6 and 30 months attending daycare in Belgium was studied shortly after the start of the epidemic (February 29th) and before the lockdown (March 18th) by performing in‐house SARS‐CoV‐2 real‐time polymerase chain reaction. No asymptomatic carriage of SARS‐CoV‐2 was detected, whereas common cold symptoms were common (51.2%). Our study shows that in Belgium, there was no sign of early introduction into daycare centers at the moment children being not yet isolated at home, although the virus was clearly circulating. It is clear that more evidence is needed to understand the actual role of young children in the transmission of SARS‐CoV‐2 and their infection risk when attending daycare.